Identification of Leaf Miner Pests and Parasitoids of The Sembalun Lombok Arabica Coffee Variety - Mega Puspita Sari; Bambang Supeno; Wahyu Astiko (Jurnal Biologi Tropis, 2026)
Arabica coffee (Coffea arabica L.) is an important plantation commodity cultivated in the Sembalun Highlands, Lombok. However, leaf miner infestations can reduce plant productivity by damaging leaf tissues and disrupting photosynthesis. This study aimed to identify leaf miner pests and associated parasitoids on several Arabica coffee varieties and to evaluate infestation intensity. The research used a quantitative desriptive approach with field survey methods. Sampling was conducted using systematic random sampling on five Arabica coffee varieties: Yellow Caturra, Red Caturra, Typica, Kobra, and Lini-S. Leaves showing leaf miner symptoms were collected weekly, reared in the laboratory, and identified morphologically. Infestation intensity was calculated using the Natawigena method and analyzed decriptively. The result showed that the leaf miner belonged to the order Lepidoptera, family Gracillariidae, genus Phyllocnistis, while the parasitoid belonged to the family Eurytomidae. The average infestation intensity was catagorized as moderate, with the highest infestation on Yellow Caturra dan the lowest on Lini-S. The presence of parasitoids indicates their potential role as biological control agents in sustainable Arabica coffee pest management.